Ergosterol Protects Canine MDCK Cells from Gentamicin-Induced Damage by Modulating Autophagy and Apoptosis - Zhipeng Qin; Liuwei Xie; Yao Wang; Na Zhang; Hailong Bi; Mingqiang Song; Chao Xu (Metabolites)
Background: Renal injury is a critical health issue in pet dogs, often exacerbated by drug-induced nephrotoxicity such as gentamicin (GM). This study investigated the protective effects of ergosterol (Erg), a natural compound from edible mushrooms, against GM-induced damage in Madin–Darby canine kidney (MDCK) cells. Methods: MDCK cells were treated with GM (0.5–3 mmol/L) for 12 h to establish injury. Erg (1 to 32 μg/mL) was pretreated for 12 h before GM exposure (2 mmol/L). Cell viability, nitric oxide (NO), lactate dehydrogenase (LDH), oxidative stress markers (SOD, GSH, CAT, MDA), inflammatory cytokines (IL-1β, IL-6, TNF-α), renal function indicators (Scr, BUN), and autophagy/apoptosis-related proteins (ATG5, Beclin1, P62, BAX, BCL-2) were assessed via CCK-8, ELISA, fluorescence staining, and Western blot. Statistical significance (p < 0.05) was determined by ANOVA and LSD post hoc tests. Results: GM (2 mmol/L) significantly reduced cell viability (p < 0.01) and elevated NO and LDH levels (p < 0.01). Erg pretreatment (4–8 μg/mL) restored cell viability (p < 0.01), suppressed NO (p < 0.01) and LDH release (p < 0.01), and enhanced antioxidant enzyme activities (SOD, GSH, CAT; p < 0.01). Erg attenuated GM-induced reactive oxygen species (ROS) overproduction (p < 0.01) and decreased pro-inflammatory cytokines (IL-1β, IL-6, TNF-α; p < 0.01). Renal markers Scr and BUN were reduced (p < 0.01). Mechanistically, Erg upregulated autophagy proteins ATG5 and Beclin1 (p < 0.01), reduced P62 accumulation (p < 0.01), and lowered the BAX/BCL-2 ratio (p < 0.01). Conclusions: Erg protects MDCK cells from GM-induced nephrotoxicity by restoring autophagy flux, suppressing mitochondrial apoptosis, and mitigating oxidative stress and inflammation. These findings highlight Erg’s potential as a natural therapeutic agent for canine renal injury. Further in vivo studies are needed to validate its clinical efficacy.